On the spectra of non-selfadjoint differential operators and their adjoints in direct sum spaces - Sobhy El-Sayed Ibrahim (International Journal of Mathematics and Mathematical Sciences)
The general ordinary quasidifferential expression Mp of nth order, with complex coefficients and its formal adjoint Mp+ on any finite number of intervals Ip=(ap,bp), p=1,…, N, are considered in the setting of the direct sums of Lwp2(ap,bp)-spaces of functions defined on each of the separate intervals. And a number of results concerning the location of the point spectra and regularity fields of general differential operators generated by such expressions are obtained.